Analisis Penerimaan Pengguna terhadap Penerapan Teknologi Informasi pada layanan Perpustakaan Digital Menggunakan Technology Acceptance Model (TAM) di Perpustakaan UNIKA Widya Karya Malang - Albertoes Pramoekti Narendra (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2022)
The digital library is a form of innovation in library services, including at the Widya Karya University Library, Malang. The application of information technology in libraries in the form of digital library services greatly provides convenience and fluency for users, however, it is necessary to know in more depth to measure the behavioral intentions of users in using digital library information technology applications or in other words there is no analysis to ensure aspects of its benefits and uses. The purpose of this paper is to find out how the acceptance of library users in utilizing information technology applications in digital library services using the Technology Acceptance Model (TAM) theoretical approach with a total sample of 22. respondents using purposive sampling technique. Analysis of the results of the calculation of Partial Least Square (PLS) to determine the variables that have an influence on attitudes and actual use. The results showed that the perceived ease of use and perceived usefulness had a significant positive effect on Attitude Toward Using. The Attitude Toward Using variable has a positive significant effect on behavioral intention to use. Behavioral intention to use have a significant positive effect on the actual system usage conditions.